Drought stress during the reproductive stage of two soybean lines - Rosa, Vanessa do Rosário; Silva, Adinan Alves da; Brito, Danielle Santos; Pereira Júnior, José Domingos; Silva, Cíntia Oliveira; Dal-Bianco, Maximiller; Oliveira, Juraci Alves de; Ribeiro, Cleberson (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the effects of drought stress in the reproductive stage (R3) on the physiological parameters and grain yield of two soybean (Glycine max) lines. The Vx-08-10819 and Vx-08-11614 soybean lines were grown in a greenhouse, where they were irrigated until they reached the R3 development stage. During three days, the weight of the pots was monitored daily in order to maintain 100, 60, and 40% field capacity (control and moderate and severe stress, respectively). The parameters gas exchange and chlorophyll a fluorescence, as well as chloroplast pigments, osmoregulatory solutes and antioxidant enzymes, were determined. After stress, the plants were rehydrated until the end of the reproductive stage (R8), to evaluate grain yield. Vx-08-10819 showed traits that contributed to drought tolerance, such as better water-use efficiency, modulation of leaf area, and enzymatic activity, as well as a more efficient photosynthetic apparatus and a lower lipid peroxidation rate than Vx-08-11614. In addition, Vx-08-10819 maintained its productivity even after the severe water deficit. By contrast, water limitations affected negatively the productivity of Vx-08-11614. The Vx-08-10819 soybean line can efficiently withstand drought periods during the reproductive stage, without any interferences on final grain yield.